Effect of Electrolytes on the Performance of Dye-Sensitized Solar Cell (DSSC) with Mulberry (Morrus) Extract as Dye Sensitizer - hikmah, irmayatul; Zahrok, ZId Latifatas; Prajitno, Gontjang (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2021)
A prototype of Dye Sensitized Solar Cell (DSSC) based TiO2 nanoparticles and mulberry (morrus) extract as dye sensitizer on the ITO glass substrate has been produced. The study aims to determine the difference between the use of gel electrolyte and liquid electrolyte on its influence on DSSC performance. Sandwich cells were made consisting of a working electrode in the form of a conductive glass ITO deposited with TiO2 which was sensitized by a dye of mulberry extract, the opposite electrode in the form of a conductive glass ITO with carbon deposited, and the electrolyte in the middle of the two electrodes were liquid and one was gel. Irradiation was carried out on both samples by lighting halogen lamps. Tested the characteristics of voltage-time and current-time in both samples. The results obtained for higher voltage and current values in samples with liquid electrolytes, but for the period of stability the samples with gel electrolytes showed better performance.